Ethical risks of systematic menstrual tracking in sport - Howe, O. R. (Journal of Bioethical Inquiry, 2024)
In this article it will be concluded that systematic menstrual tracking in women`s sport has the potential to cause harm to athletes. Since the ruling of Dobbs v. Jackson Women`s Health Organization (2022) in the United States, concerns regarding menstrual health tracking have arisen. Research suggests that the menstrual tracking of female athletes presents potential risks to "women`s autonomy, privacy, and safety in sport" (Casto 2022, 1725). At present, the repercussions of systematic menstrual tracking are particularly under-scrutinized, and this paper seeks to combine novel research in the sport sciences with present ethical debates in the philosophy of sports. Utilizing Beauvoir`s feminist philosophy (2011), this paper argues that systematic menstrual tracking may contribute to the wider system of women`s oppression by exploiting female athletes, as well as enabling the internalization of submissive behaviour in cultures where athletes are expected to comply unquestioningly. Five policy recommendations are made concerning autonomy, informed consent, education, safeguarding and data access. The overall findings of this paper propose that a more in-depth understanding of the links between data, privacy, and the menstrual cycle are required by sports organizations and governing bodies if athletes are to be protected in a future where systematic menstrual tracking is inevitable.